The voice of southern labor : radio, music, and textile strikes, 1929-1934 - Roscigno, Vincent J. (Social movements, protest, and contention ;, 2004)
The Voice of Southern Labor chronicles the experiences of southern textile workers and provides a unique perspective on the social, cultural, and historical forces that came into play when the group struck in 1934. The workers' grievances and solidarity were reflected in the music they listened to and sang, and this book offers a context for this intersection of labor, politics, and culture.